Effect of Five Weeks Circuit Resistance Training with Garlic Supplementation on Serum Levels of Adiponectin in Over Weight Female - Zeynab Hamidnejad; Seyed Mohsen Avandi; Rohollah Haghshenas; Abbas Pakdel (Institue of Medicinal Plants, ACECR, 2017)
Background: Obesity and Metabolic Disorders is one of the risk factors for health in the world. Physical activity and herbal supplements is the research topic in the field of health and reducing obesity. Objective: The purpose of this study was to compare the effect of five weeks circuit resistance training with garlic supplementation on serum levels of adiponectin in over weight female. Methods: In a double-blind trial quasi-experimental design, 32 healthy overweight women were selected and randomly divided into following four groups: Placebo, supplement, training and placebo and training and supplement groups. The experimental subjects received circuit resistance training was performed three times a week. All groups were given 1000 mg garlic supplements or placebo for five weeks in two doses of 500 mg daily. Anthropometric indices, and blood sampling were measured before and after five weeks of circuit resistance training. Results: After five weeks, levels of adiponectin in serum increased in resistance training group with garlic with compared to other groups, but this increase was not statistically significant (p=0.123) also body weight did not show significant difference (P=0.99). Conclusion: Based on the results suggested that more research investigate effect of garlic supplementation with resistance exercise on weight loss and serum adiponectin levels and other indicators associated with obesity in obese women.